Two-dimensional hydrogenated molybdenum and tungsten dinitrides MN2H2 (M = Mo, W) as novel quantum spin hall insulators with high stability. Issue 3 (23rd December 2016) - Liu, Peng-Fei; Zhou, Liujiang; Frauenheim, Thomas; Wu, Li-Ming
Abstract : Hydrogenation enhances the structural stability and brings about the intrinsic quantum spin Hall effect in MoS2 -like MoN2 and WN2 sheets. Abstract : Based on first-principles calculations, we predict the existence of the quantum spin Hall (QSH) effect in hydrogenated transition-metal nitrides MN2 H2 (M = Mo, W), showing high structural stability. MN2 H2 monolayers are identified to be intrinsic topological insulators (TIs) with protected Dirac type topological helical edge states, and show robust topological features against the large stretching strain. Besides, sizeable intrinsic nontrivial band gaps (70–124 meV) ensure the QSH effect in MN2 H2 at room temperature. The pure d–d band inversion was revealed. More interestingly, the topological phase transition between a QSH phase and a topological semimetallic phase can be induced by applying in-plane strain.